Balancing safety, efficacy and cost: Improving rotavirus vaccine adoption in low- and middle-income countries - Anant Bhan; Shane K. Green (Edinburgh University Global Health Society, 2011)
Diarrheal disease caused by rotavirus claims approximately 500 000 lives each year, mostly in low-income countries. Many of these deaths are preventable through the use of available rotavirus vaccines. Yet, in spite of a WHO recommendation that these vaccines be adopted into all national immunization programs, only a few countries have done so.